2021
DOI: 10.25259/ijdvl_106_20
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution ultrasound in the assessment of peripheral nerves in leprosy: A comparative cross-sectional study

Abstract: Background: Detection of peripheral nerve thickening and nerve function impairment is crucial in the diagnosis and the management of leprosy. Aims and objectives: (1) To document the cross-sectional area, echotexture and blood flow of peripheral nerves in healthy controls and leprosy cases using high-resolution ultrasound, (2) to compare the sensitivities of clinical examination and high-resolution ultrasound in detecting peripheral nerve thickening in leprosy. Methods: Peripheral nerves of 30 leprosy pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…6 Recently, Sreejith et al also reported a lack of good agreement between clinical and sonographic examination for the detection of thickened nerves with a kappa of −0.04 for the median nerve to 0.215 for the common peroneal nerve. 7 These data clearly indicate clinical examination alone is inadequate and HRUS identifies a greater number of patients with abnormal nerves even in the presence of normal electrophysiological testing. 8 Sonographically enlarged nerves correlate with clinical and electrophysiological abnormalities.…”
Section: Superiority Of Ultrasound Above Clinical Palpation To Detect Nerve Thickeningmentioning
confidence: 93%
See 1 more Smart Citation
“…6 Recently, Sreejith et al also reported a lack of good agreement between clinical and sonographic examination for the detection of thickened nerves with a kappa of −0.04 for the median nerve to 0.215 for the common peroneal nerve. 7 These data clearly indicate clinical examination alone is inadequate and HRUS identifies a greater number of patients with abnormal nerves even in the presence of normal electrophysiological testing. 8 Sonographically enlarged nerves correlate with clinical and electrophysiological abnormalities.…”
Section: Superiority Of Ultrasound Above Clinical Palpation To Detect Nerve Thickeningmentioning
confidence: 93%
“…8 Sonographically enlarged nerves correlate with clinical and electrophysiological abnormalities. 7,9 Being non-invasive and well tolerated by the patients, HRUS can be used to identify 'silent' neuropathy in patients with isolated cutaneous manifestations and normal neurological examination, as well as to screen household contacts. With technological advances, smaller ultrasound machines are available which can be used at the point-of-care.…”
Section: Superiority Of Ultrasound Above Clinical Palpation To Detect Nerve Thickeningmentioning
confidence: 99%
“…Presence of hypo- or anaesthetic hypopigmented lesions during assessment, and thickened peripheral nerves identified via palpation or ultrasonography, are key diagnostic features of leprosy. 73 75 Confirmatory laboratory testing to detect acid-fast bacilli in slit skin smears or biopsies using Fite staining and light microscopy or polymerase chain reaction (PCR) amplification can also be completed. Diagnostic specimens are preferentially collected from persistent and active lesions typically located in cooler parts of the body.…”
Section: Leprosymentioning
confidence: 99%
“…Recently, high-frequency ultrasound with color Doppler (HFUS with CD) have been used to describe characteristic changes in leprosy neuropathy to further facilitate diagnosis and treatment. Studies have described nerve thickening at entrapment sites, cross-sectional area difference between tuberculoid and lepromatous diseases, and increased intraneural or perineural vascularization [161][162][163][164][165].…”
Section: High-resolution Ultrasonography With Color Dopplermentioning
confidence: 99%